Gut Microbiome Differences in Rescued Common Kestrels (Falco tinnunculus) Before and After Captivity - Zhang, Kangqing; Wang, Xinxiang; Gong, Xiang; Sui, Jinling (Frontiers in Microbiology, 2022)
Gut microbes significantly impact animal health, yet research on the gut microbiota of most birds, especially raptors, is lacking. This study investigated the effects of dietary and environmental changes on the composition and abundance of gut microbiota in 17 rescued common kestrels (Falco tinnunculus) through 16S rRNA gene high-throughput sequencing of microorganisms in the feces of the birds. Firmicutes (relative abundance, 43.63%), Proteobacteria (37.26%), Actinobacteria (7.31%), and Bacteroidetes (5.48%) were the dominant phyla in the gut microbiota of the common kestrels. A comparison of the gut microbiota before and after captivity revealed that community composition and abundance of the common kestrel gut microbiota differed among different living conditions including diet and environment. At the phylum level, the abundance of Firmicutes was higher (P < 0.05), and that of Proteobacteria was lower (P < 0.05), after captivity (54.62% and 27.16%, respectively) compared with before captivity (33.67% and 46.41%, respectively), but no significant differences were found among other phyla. At the genus level, the abundance of Lactobacillus was higher (P < 0.05) after captivity (15.77%) compared with the abundance before captivity (5.02%). Hierarchical clustering and principal component analyses showed that common kestrels in different living conditions exhibited differences (P < 0.05) in gut microbiota at phylum and genus levels. Functional prediction of gene sequences using PICRUSt2 further revealed that pathways related to glucose metabolism and amino acid metabolism were enhanced (P < 0.05) after captivity. Collectively, the findings from this study demonstrated that the relative abundance of specific microbes in the gut of the rescued common kestrels either increased or decreased, and that dietary and environment changes might be the predominant factors affecting the gut microbiota of these birds during rescue or captivity.